2016
DOI: 10.1159/000445102
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Tumor Necrosis Factor-Alpha: A Role for Adalimumab in Neovascular Age-Related Macular Degeneration Refractory to Anti-Angiogenesis Therapy

Abstract: Aims: To report a case of wet age-related macular degeneration (wet-AMD) refractory to intravitreal anti-vascular endothelial growth factor (anti-VEGF) therapy in a patient who showed visual and anatomical improvement and stabilization after starting a subcutaneous treatment course with adalimumab, an anti-tumor necrosis factor-alpha (TNF-α) drug, for concomitant Crohn's disease. Methods: Observational case report of a female patient. Ophthalmological evaluation was performed by slit lamp and ophthalmoscopy (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…It is well established that the TNF pathway is a key mediator of inflammation in many ocular diseases including diabetic retinopathy, uveitis, proliferative vitreoretinopathy, macular edema and wet AMD 17 , 66 . We previously showed that in the early stages of rcd1 and xlpra2 disease, TNF-superfamily members are upregulated and may thus contribute to the disease pathogenicity 10 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the TNF pathway is a key mediator of inflammation in many ocular diseases including diabetic retinopathy, uveitis, proliferative vitreoretinopathy, macular edema and wet AMD 17 , 66 . We previously showed that in the early stages of rcd1 and xlpra2 disease, TNF-superfamily members are upregulated and may thus contribute to the disease pathogenicity 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being an inducer of the NF‐κB pathway, TNFα presents increased expression with human ageing and in age‐related degenerative diseases such as Alzheimer's disease . Importantly in relation to the RPE, TNFα was shown to increase the production and secretion of the angiogenic VEGF protein, a known contributor to development of wet (neovascular) AMD, and anti‐TNFα injections helped improve vision of wet AMD patients …”
Section: Discussionmentioning
confidence: 99%
“…TNF-α acts as a proinflammatory cytokine that is produced by macrophages and T cells 23. As a powerful proinflammatory cytokine, TNF-α has been targeted in RA2428 as well as neovascular AMD therapies,29 and recent findings have supported interactions between TNF-α and the complement system 30,31. Biologics targeting TNF-α, such as infliximab, adalimumab, and etanercept, are currently approved treatments for RA by the US Food and Drug Administration.…”
mentioning
confidence: 99%